2017
DOI: 10.1177/0018578717746369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Clinical Decision Support Tool on Cancer Pain Management in Opioid-Tolerant Inpatients

Abstract: Pain is both common and undertreated in the hematology/oncology population despite national guidelines and a focus from The Joint Commission. Herein, we describe the features of a pain clinical decision support tool (PCDST) embedded into the electronic medical record (EMR) and report its impact on oncology inpatients at risk for uncontrolled pain. The PCDST was developed to identify patients with potentially uncontrolled pain, defined as a pain score ≥4. Clinical pharmacists were encouraged to use the tool to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Bertsche et al showed no significant change in pain intensity score (NVAS) on day 5 after admission, after implementation of a CDSS [34]. Similar, Christ et al showed no significant difference in mean pain score at hospital admission and after 28 h [28].…”
Section: Clinical Outcomesmentioning
confidence: 94%
See 4 more Smart Citations
“…Bertsche et al showed no significant change in pain intensity score (NVAS) on day 5 after admission, after implementation of a CDSS [34]. Similar, Christ et al showed no significant difference in mean pain score at hospital admission and after 28 h [28].…”
Section: Clinical Outcomesmentioning
confidence: 94%
“…Six studies targeted multiple specialisms; the others focused on one specialism. CDSSs of included studies focused on risk assessment or therapy options to support informed decisions [26][27][28][29][30][31][32], as well as statistical methods and data mining to generate patient-specific recommendations [33,34]. For most studies (7/9), clinical guidelines formed the knowledge base of the CDSS.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 3 more Smart Citations